CORRELATION BETWEEN MEDICAL STUDENTS’ PERCEPTION OF ONLINE LECTURE AND LEARNING MOTIVATION DURING THE LOCKDOWN: A SINGLE INSTITUTION PERSPECTIVE - Laksmitasari Dewi; Hemma Yulfi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Since it was first declared global pandemic by WHO in March 2020, Covid-19 has been triggered many unprecedented changes in education. This drastic change is likely to have an impact on students’ perception and their scholastic motivation. Many previous studies have discussed students’ perception towards online learning and students’ learning motivation during this pandemic separately, but we found none discussed on their relationship.Aims: This study ventured to distinguish a possible correlation between perception of online learning and learning motivation among the students in Faculty of Medicine, Universitas Sumatera Utara, during the pandemic lockdown.Methods: This was a correlative study with a cross-sectional design. Subjects were 286 students, selected from three academic years. Primary data was collected by using questionnaire. Data was analysed with Spearman’s rank test and binary logistics to find true association by using IBM SPSS for Windows 26.0.Results: Students’ perception of online lecture were mostly towards favourable attitude, while students’ learning motivation was leaning towards lower motivation. We found an interesting finding regarding the correlation of both variables. Descriptively, students found that they were easily lose focus during online session. Most of the students also perceived that online learning is less effective compared to face-to face learning.Conclusion: Online learning faces hinderances, both technically and psychologically. Faculty and educators need to address these challenges to be able to promote better strategy in dealing with the difficulties